2012
DOI: 10.1111/j.1476-5829.2011.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐mesenchymal transition as a fundamental mechanism underlying the cancer phenotype

Abstract: Epithelial-mesenchymal transition (EMT) is a complex process involved in embryonic development, wound healing and carcinogenesis. During this process, epithelial cells lose their defining characteristics and acquire mesenchymal properties: loss of cell-cell adhesion; increased motility and invasiveness; resistance to apoptosis and changes in cellular morphology. EMT has been implicated as a driver of metastasis and tumour invasion, as this process allows cells to detach from their niche and migrate through blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 92 publications
0
63
0
Order By: Relevance
“…EMT is an important basis for obtaining the malignant phenotype of hepatocytes (4). Moreover, Cx-mediated GJ has recently been proposed to serve as an intercellular glue to suppress EMT and cancer metastasis (9), we thus explored the role of EMT in Cx32-mediated function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is an important basis for obtaining the malignant phenotype of hepatocytes (4). Moreover, Cx-mediated GJ has recently been proposed to serve as an intercellular glue to suppress EMT and cancer metastasis (9), we thus explored the role of EMT in Cx32-mediated function.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, cells lose polarity, cell-cell adhesion, epithelial markers such as E-cadherin, and acquire mesenchymal properties with high expression of mesenchymal molecular markers including vimentin, Snail, Slug and Twist (4). A number of studies have shown that EMT plays a crucial role in liver cancer invasion and metastasis (57), nevertheless, there is a lack of clear picture in HCC of the overall EMT signaling network.…”
Section: Introductionmentioning
confidence: 99%
“…2a, b). The loss of E-cadherin signifies a reduction in cell-cell adhesion and a shift of the prostate luminal cells from a clearly differentiated epithelial to a more mesenchymal phenotype and also an early stage of transformation [33, 34]. The disrupted expression of basal cell marker p63 in the prostate gland from the pbIL-6 mice also signifies the early transformation events of the prostate [35, 36] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of IGF signaling axis has been shown to play an essential role in tumor cell survival and proliferation [33]. In pbIL-6 mice, a significantly increased expression IGF-I and IGF-II was demonstrated by quantitative RT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PMA exposure resulted in decreased mRNA expression of E-cadherin and enhanced mRNA expression of vimentin (Fig. 7B), that 14 also represent key hall-marks of EMT [40]. Reduced expression of E-cadherin protein concomitantly occurred in response to PMA, as demonstrated by Western-blotting (Fig.…”
Section: Association Of Pma-induced Transporter Expression Changes Wimentioning
confidence: 85%